Steric Control in Reactions of N‐Heterocyclic Phosphorus Electrophiles with Pentacarbonyl Manganate(–I). Issue 17 (25th June 2018) - Papendick, Marius; Feil, Christoph M.; Nieger, Martin; Gudat, Dietrich
Abstract : Metathesis of Na[Mn(CO)5 ] with N‐ t Bu and N‐Mes substituted, electrophilic N‐heterocyclic phosphane derivatives afforded in the first case an ionic N‐heterocyclic phosphenium (NHP) metalate and in the second case a covalent phosphenium complex. The products were characterized by analytical and spectroscopic data and the NHP complex as well by a single‐crystal X‐ray diffraction study. A DFT study allows relating the different outcome of the reactions studied with the energetics of the decarbonylation of the appropriate NHP metalates. Closer evaluation reveals steric factors as the key to explaining the observed behavior, and indicates that their impact displays close parallels to NHC chemistry. Abstract :